Making Muslim space in North America and Europe - Metcalf, Barbara, 1941- (Berkeley : University of California Press, 1996)
Focusing on the private and public use of space, this volume explores the religious life of the new Muslim communities in North America and Europe. Unlike most studies of immigrant groups, these essays concentrate on cultural practices and expressions of everyday life rather than on the political issues that dominate today's headlines. The authors emphasize the cultural strength and creativity of communities that draw upon Islamic symbols and practices to define "Muslim space" against the background of a non-Muslim environment. -- The range of perspectives is broad, encompassing middle-class professionals, mosque congregations, factory workers in France and the north of England, itinerant African traders, and prison inmates in New York. The truism that "Islam is a religion of the word" takes on concrete meaning as these disparate communities find ways to elaborate word-centered ritual and to have the visual and aural presence of sacred words in the spaces they inhabit. -- Publisher description
Introduction : Sacred words, sanctioned practice, new communities / Barbara D. Metcalf -- Muslim space and the practice of architecture :a personal odyssey / Gulzar Haidar -- Transcending space : recitation and community among South Asian Muslims in Canada / Regula Burckhardt Qureshi -- "This is a Muslim home" : signs of difference in the African-American row house / Aminah Beverly McCloud -- "Refuge" and "prison" : Islam, ethnicity, and the adaptation of space in workers' housing in France / Moustapha Diop and Laurence Michalak -- Making room versus creating space : the construction of spatial categories by itinerant Mouride traders / Victoria Ebin -- New medinas : the Tablighi Jamaʻat in American and Europe / Barbara D. Metcalf -- Island in a sea of ignorance : dimensions of the prison mosque / Robert Dannin, with photographs by Jolie Stahl -- A place of their own : contesting places and defining places in Berlin's migrant community / Ruth Mandel -- Stamping the earth with the name of Allah : zikr and the sacralizing of space among British Muslims / Pnina Werbner -- Karbala as sacred space among North American Shiʻa : "Every day is Ashura, everywhere is Karbala: / Vernon James Schubel -- The Muslim World Day Parade and "storefront" mosques of New York city / Susan Slyomovics -- Nationalism, community, and the Islamization of space in London / John Eade -- Engendering Muslim identities : deterritorialization and the ethnicization process in France / Rachel Bloud.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Muslims -- North America; Muslims -- Europe; Musulmans -- Amérique du Nord; Musulmans -- Europe; RELIGION -- Islam -- Rituals & Practice; RELIGION / Islam / General; Muslims; Europe; North America; Diaspora; Islam; Muslim; Europa; Nordamerika; Aufsatzsammlung; Islamieten; Religieuze opvattingen; Architecture islamique -- Amérique du Nord; Architecture islamique -- Europe; Musulmans -- Amérique du Nord; Musulmans -- Europe